Investigation of Giardia lamblia and other parasites in tap water as a potential source of transmission in some regions of Baghdad - M. Al-Sagur, Ihsan; H. Mahmood, Souhaila; M. A. Al-Obaidi, Heba (Iraqi Journal of Science, 2023)
Samples from tap water were chosen to be examined as one of the possible modes of G. lamblia and other parasites transmission. 144 domestic filter units were randomly distributed to houses in Baghdad in Al-Sadr City and surrounding regions then the suspended materials were examined microscopically by direct wet mount after centrifugal sedimentation method, and after staining with modified Ziehl-Neelsen (acid fast) stain. The results showed that 5/144 (3.47%) samples contained G. lamblia cysts, 3/144 (2.08%) contained E. histolytica/E. dispar cyst, while each of Cryptosporidium spp. and Cyclospora cayetanensis oocysts were observed in two samples (1.38%); also free living amoeba, ciliates and flagellates were detected in all samples. This result reveals a potential role of drinking water in the infection with these intestinal parasites in the study's area. Accordingly, the present study recommends the need to ensure the purification and sterilize drinking water and the safety of pipeline network. On the other hand, this new method, at the local level, by using domestic filter units for the detection of parasites and other microorganisms in tap water provide a simple, effective, and applicable research's tool beside saving time and effort in the samples' collection and filtration.